A fault dynamic model of high-speed angular contact ball bearings. (January 2020) - Qin, Yi; Li, Chengcheng; Cao, Folin; Chen, Haizhou
Highlights: A new dynamic model of faulty high-speed angular contact ball bearings is set up. A B-spline fitting excitation function is used to represent the fault excitation. The dynamic responses under different fault sizes and speeds are compared. Experiment on high-speed bearings was performed to verify the proposed model. Abstract: Angular contact ball bearings (ACBBs) are widely used in rotary machines especially in high-speed rotating machines because of their excellent properties. However, the traditional dynamic model of a rolling bearing is mainly applied to simulate the dynamic response at low speed, and uses the simple displacement excitation function to characterize the fault, thus its accuracy will decrease under high speed condition. Aiming at the shortcomings of the traditional model, a new high-speed fault dynamic model of ACBB is proposed by considering the influences of centrifugal force, gyroscopic moment and time-varying contact angles on the rolling element under high-speed running and using a B-spline fitting displacement excitation method to represent the fault excitation. With this model, high-speed dynamic responses under different fault sizes and rotation speeds are calculated by the Runge–Kutta method and Newton– Raphson method. Then the corresponding time and frequency domain characteristics are analyzed. From the simulation results, it can be seen that all the simulated acceleration signals of ACBBs are more in line with the actual situation than the traditional model, especially for the shape of an impulse. Finally, the effectiveness and correctness of the proposed model are verified by the experiment on aero-engine spindle bearings.